Les catastrophes futures ou les futurs de la catastrophe : les désastres à venir dans Jouer le Paradis et Let Them Eat Money - Eliane Beaufils (ReS Futurae)
The two plays Play the Paradise and Let Them Eat Money are fictions focussing on the coming climate catastrophe. Both are structured along clear narratives : they are anchored in the present et anticipate future disasters on a social and individual level. Though they range among the rare climate-fictions in drama, their dramaturgical strategies diverge. So does their vision of catastrophe, related to two different, maybe complementary ethics. Let Them Eat Money takes place in the fictive year 2028, ten years after the production of the performance. It is situated in an European environment derived from the present one. The protagonists pretend to do justice and to avenge the faults of the rulers since 2018. Play the Paradise proceeds metaphorically. The different narrations seem to be contemporary but they drift in an unsituated catastrophe. The plots result in a very different confrontation to catastrophe. Let Them Eat Money may seem post-Brechtian because of its very rich material as well as its concentration on past and present choices. But it paves the way to a strong determinism and the spectators are confronted to an array of errors or hamartias. The play shows the stalemate of traditional ethics (Jonas). Play the Paradise conversely blurs the situations, so that the catastrophes contaminate the present. The narrator is plunged into grief. By its poetic writing the play also invites the spectators to deal with sorrow and grieving.